Acute aseptic meningitis due to intravenous immunoglobulin therapy in Guillain–Barré syndrome. Issue 7 (29th October 2014) - Jain, Rajendra Singh; Kumar, Sunil; Aggarwal, Rakesh; Kookna, Jagdeesh Chandra
Abstract : The majority of adverse reactions of intravenous immunoglobulin (IVIG) therapy are mild, transient and self-limiting with potentially serious complications occurring in <5% of patients. IVIG-associated transient aseptic meningitis is one such rare adverse effect, which has been seldomly described in the literature. We report a case of aseptic meningitis due to IVIG therapy in a Guillain–Barré syndrome (GBS) patient. The cerebrospinal fluid analysis revealed high cell counts with predominance of lymphocytic cells, raised protein, normal glucose level and no growth of the organisms on culture. The patient improved with supportive care such as intravenous fluids and analgesics without neurological complications. This case emphasizes the importance of recognizing IVIG-associated complications like aseptic meningitis in GBS patients.